First insight into plastics ingestion by fish in the Gulf of California, Mexico. (October 2021) - Salazar-Pérez, C.; Amezcua, F.; Rosales-Valencia, A.; Green, L.; Pollorena-Melendrez, J.E.; Sarmiento-Martínez, M.A.; Tomita Ramírez, I.; Gil-Manrique, B.D.; Hernandez-Lozano, M.Y.; Muro-Torres, V.M.; Green-Ruiz, C.; Piñon-Colin, T.D.J.; et al.
Abstract: Plastic particle occurrence in the digestive tracts of fishes from a tropical estuarine system in the Gulf of California was investigated. A total of 1095 fish were analysed, representing 15 species. In total 1384 particles of plastic debris were recovered from the gastrointestinal tracts of 552 specimens belonging to 13 species, and all consisted of threads, the majority of which were small microplastics (0.23 to 1.89), followed by large microplastics (2.07 to 4.49), and few mesoplastics (5.4 to 19.86). Plastic particles were identified using ATR-FTIR spectroscopy. The mean frequency of occurrence of plastics in the gastrointestinal tracts of fishes from this system was 50.5%, which is higher than frequencies reported in similar systems in other areas. The polymers identified by ATR-FTIR were polyamide (51.2%), polyethylene (36.6%), polypropylene (7.3%), and polyacrylic (4.9%). These results show the first evidence of plastic contamination for estuarine biota in the Gulf of California. Highlights: The presence of plastic debris in gastric contents of teleost fish in the Gulf of California is confirmed. Its frequency of occurrence is much higher than those reported from similar ecosystems. The most abundant polymer was nylon, indicating a high polution from small scale commercial fishing gear and textiles.